Cutaneous Ulcers as Initial Presentation of Localized Granulomatosis with Polyangiitis: A Case Report and Review of the Literature - Noreen Nasir; Syed Ahsan Ali; Hafiz Mohammed Mehmood Riaz (Case Reports in Rheumatology)
Background. Granulomatosis with polyangiitis (GPA) is an ANCA associated small vessel vasculitis characterized by necrotizing granulomatous inflammation involving the upper and the lower respiratory tract and the kidneys. The disease has a broad clinical spectrum that ranges from limited/localized involvement of a single organ system to a generalized systemic vasculitis that affects several organs with evidence of end organ damage. Atypical forms of the disease have been recognized with or without respiratory tract involvement with a long protracted course before manifesting as generalized disease. Case Presentation. We describe a 57-year-old woman who presented with recurrent fever and cutaneous ulcers on her legs who was diagnosed to have granulomatosis with polyangiitis (GPA) after an extensive evaluation which excluded infectious, other vasculitides, connective tissue disease and malignant etiologies. Conclusion. In the absence of typical manifestations, granulomatosis with polyangiitis (GPA) is indeed a diagnostic challenge to the physician. Atypical manifestations like unexplained recurrent fever and cutaneous ulcers nevertheless call for keeping a low threshold for the diagnosis of GPA as the disease can initially present in localized form before heralding into a generalized disease.